Social Spending and Poverty Reduction in Mexico from 2000 to 2022: Have States Contributed to It? - Anahely Medrano; Brisna Beltrán (Sobre México)
Poverty is a major socio-economic problem in Mexico. At the national level, 36.3% of the population lived below the official poverty line in 2022. Although poverty rates varied across states, they have remained rather stable on average from 2000 to 2020. At the same time, social spending at the state level, in general, has maintained a relatively increasing trend in the last two decades. However, analysis of social spending and poverty at the subnational level is still scarce in Mexico. This study aims to analyze the impact of total and sectoral social spending on poverty reduction at the state level, from 2000 to 2022. This analysis uses novel data from state public accounts of the thirty-one states and Mexico City. The results of this study show that there is no significant relationship between total social spending and extreme income poverty and multidimensional poverty at the state level. However, extreme income poverty and healthcare and education spending showed a negative relationship. These results suggest that, on average, the social investment of states has had a rather meager effect in terms of poverty reduction in Mexico.